1982
DOI: 10.1007/bf01323753
|View full text |Cite
|
Sign up to set email alerts
|

Haematological studies on90Sr-90Y-toxicity: II. Femoral CFU-s kinetics and mitogen response of spleen cells

Abstract: Ferrokinetic perturbations in peripheral blood of mice treated with 90Sr-90Y were demonstrated previously. This paper deals with the effects of 90Sr-90Y treatment (2.5, 5, and 10 microCi/mouse), on the haemopoietic stem cell compartment and on the immune-status. The frequency and kinetics of haemopoietic stem cells in femoral marrow (determined as colony forming units in spleen, CFU-s) and their haemopoietic efficiency (as gauged by 59Fe- and 125IUdR-uptake) were estimated. The responsiveness of splenic lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, compared to beta emitters, the toxic effects on hematopoiesis are less frequent with 223 Ra [ 9 ]. It has been published that radiotherapy with beta and gamma isotopes induces numerical and also functional changes in leukocytes [ 11 , 12 , 13 , 14 , 15 ]. In line with only mild effects of 223 Ra, our group showed that in eleven patients with metastasized, castration-resistant prostate cancer one cycle of treatment with this alpha-emitter did not significantly impair lymphocyte function in vitro [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to beta emitters, the toxic effects on hematopoiesis are less frequent with 223 Ra [ 9 ]. It has been published that radiotherapy with beta and gamma isotopes induces numerical and also functional changes in leukocytes [ 11 , 12 , 13 , 14 , 15 ]. In line with only mild effects of 223 Ra, our group showed that in eleven patients with metastasized, castration-resistant prostate cancer one cycle of treatment with this alpha-emitter did not significantly impair lymphocyte function in vitro [ 16 ].…”
Section: Introductionmentioning
confidence: 99%